THE INFLUENCE OF SIMULATION METHOD AT SOCIAL SCIENCE LEARNING AS DISASTER MITIGATION EDUCATION OF MOUNT KELUD IN KEDIRI ELEMENTARY SCHOOL - Sandra Diah Ayu Pitalok; Tera Noviantiningtyas Ripto Saputri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The 2013 curriculum emphasizes learning using the scientific approach. In fact, many teachers still use conventional learning methods so that it impacts on student activity in the learning process. Moreover, the material taught is not related to concrete situations. The simulation method can be used to improve student learning outcomes in 4th grade in social science KD 4.2. The purpose of this study was to determine the effect of the simulation method on the ability to distinguish regions affected by the Mount Kelud eruption and to know the effect of the simulation method on the ability to demonstrate the mitigation efforts of the Mount Kelud eruption as a volcano in elementary school students in Kediri. The results of this study indicated: (1) based on the test results obtained tcount = 9.531> ttable = 2.032 with a significance level of 0.05, there were differences in the results of the average pre-test with post-test which meant that there was an influence of using the simulation method on the ability of students to distinguish regions affected by the eruption of Mount Kelud; (2) based on the test results obtained tcount = 12.063> ttable = 2.032 with a significance level of 0.05, there were differences in the results of the average non-simulation with simulation, which meant that there was an influence of using the simulation method on the ability to demonstrate mitigation efforts in eruption of the Kelud as a volcano